Names of buildings and places in the Alun-Alun Lor and Sasana Suméwa Complex of Surakarta Hadiningrat Sunanate Palace: Morphological process approaches in Linguistic Landscape - Manumanasa, Sindhu Linguistika (Universitas Dian Nuswantoro, 2025)
Naming is the process of naming or identifying something, be it an item, person, place, or concept. It is an essential part of human language and communication as it allows us to convey information, distinguish people from one another, and refer to things in writing or conversation. However, naming can become more complex and varied as culture and language evolve. In Keraton Kasunanan Surakarta Hadiningrat, names that reflect Javanese culture are used to name places and buildings. In the naming process, factors such as language, culture, and history should be considered. This research aims to describe the naming process and explain the morphological process that occurs in the names of buildings and places in the Alun-Alun Lor and Sasana Suméwa complexes. The source of data and data in this study are the names of buildings and places in the Alun-Alun Lor and Sasana Suméwa complexes of Surakarta Hadiningrat Sunanate Palace. The data were collected using observation methods with note and listening techniques, interview methods, and document analysis. The results showed 22 names of buildings and places in Alun-Alun Lor and Sasana Suméwa complexes, consisting of 14 names in Alun-Alun Lor complex and 8 names in Sasana Suméwa complex